PERICARDIAL FLUID BIOCHEMISTRY FOR THE ESTIMATION OF TIME SINCE DEATH: A PROSPECTIVE STUDY (Journal of Forensic Medicine & Toxicology, 2018)
Background: Time of death is a big issue in the investigation of an unwitnessed death. Autopsy’s conventional method of determining time since death (TSD) are found to be inaccurate and unreliable. It has been suggested that post-mortem biochemistry of pericardial fluid may play a role in TSD. The aim of the study was to determine the correlation of time since death with the biochemical changes in the pericardial fluid. Material & Methods: pH, total protein, Sodium (Na), Potassium (K), Creatinine, Transaminase (GOT & GPT) were estimated in the pericardial fluid from 78 dead bodies with known TSD. Cases are grouped according to their cause of death. All the deaths were grouped in to two types. Regression analysis to establish the correlation of these biochemical values with time since death is presented. Results: Mean age of the participants was 30.6 (±13.2) years and majority of them were males (76.9%). Nearly half of them (43.6%) died due to cranio-cerebral damage. Correlation of TSD with the pH of the pericardial fluid in association with potassium in spot deaths appears to be significant. On multiple regression analysis of TSD on considering pH and potassium together of spot deaths, relationship was found to be improved with explained variation of 7.18%. Conclusion: Pericardial levels of pH decreased with the time elapsing after the death in spot death cases as compared to those deaths who had survival time.Potassium were significantly correlated with time since death. Assessment of the TSD in spot death can be made with more accuracy by an equation.
Keywords: pericardial fluid; fingers; Balasooriya